A Diagnosis of Maxillary Sinus Fracture with Cone-Beam CT: Case Report and Literature Review - Yilmaz, Selmi Yardimci (Thieme Medical Publishers, 2014)
The purpose of this article is to present the case of maxillofacial trauma patient with maxillary sinus fracture diagnosed with cone-beam computed tomography (CBCT) and to explore the applications of this technique in evaluating the maxillofacial region. A 23-year-old male patient attempted to our clinic who had an injury at midface with complaints of swelling, numbness. The patient was examined before in emergency center but any diagnosis was made about the maxillofacial trauma. The patient re-examined clinically and radiographically. A fracture on the frontal wall of maxillary sinus is determined with the aid of CBCT. The patient consulted with the department of maxillofacial surgery and it is decided that any surgical treatment was not necessary. The emerging technique CBCT would not be the primary choice of imaging maxillofacial trauma. Nevertheless, when advantages considered this imaging procedure could be the modality of choice according to the case.